2007
DOI: 10.1016/j.heares.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Marker retention in the cochlea following injections through the round window membrane

Abstract: Local delivery of drugs to the inner ear is increasingly being used in both clinical and experimental studies. Although direct injection of drugs into perilymph appears to be the most promising way of administering drugs quantitatively, no studies have yet demonstrated the pharmacokinetics in perilymph following direct injections. In this study, we have investigated the retention of substance in perilymph following a single injection into the basal turn of scala tympani (ST). The substance injected was a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…More consistent and efficient delivery would be expected when the solution was directly injected into perilymph. With applications by intracochlear injection into the cochlear apex [Salt et al 2006] or by injections through the RW membrane [Salt et al 2007, Hahn et al 2012], concentrations in perilymph were found to be higher, with lower variation and the substances were distributed more uniformly along scala tympani. Effective deliveries of viral vectors have been accomplished with single intracochlear injection procedures [Stover et al 1999; Kawamoto et al, 2001; Staecker et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…More consistent and efficient delivery would be expected when the solution was directly injected into perilymph. With applications by intracochlear injection into the cochlear apex [Salt et al 2006] or by injections through the RW membrane [Salt et al 2007, Hahn et al 2012], concentrations in perilymph were found to be higher, with lower variation and the substances were distributed more uniformly along scala tympani. Effective deliveries of viral vectors have been accomplished with single intracochlear injection procedures [Stover et al 1999; Kawamoto et al, 2001; Staecker et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, it is necessary to obtain longer delivery time with constant drug concentrations. In the guinea pig, perilymph fluid leakage and diffusion toward the cochlear aqueduct can noticeably affect the drug concentration in the middle and upper turns when locally administered as a bolus [19]. In the human, the cochlear aqueduct is not as wide as in the animal but pericochlear leakage during intraoperative injection might affect the drug diffusion, therefore delivery away from cochleostomy and deep inside the cochlea might be more efficient in reaching the apical hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…For low injection rates, the induced rate of perilymph flow may be low, and spread from the injection site will be dominated by diffusion. This has been demonstrated both by real-time measurements of markers [67] and by functional measures during pulsed injections into the basal turn of the ST [68]. For higher injection rates, the spread of drug can only be predicted if the fluid outlet site is known.…”
Section: Delivery Systems and Protocolsmentioning
confidence: 99%
“…However, when perilymph concentration was measured following injections through the RWM with fine (20-µ M OD) bevelled pipettes held in a micromanipulator, small leaks around the pipettes caused significant washout of the drug [67]. It was calculated that the leakage rate under these conditions averaged just 90 nl/min, which was sufficient to wash out the drug but was not visible with an operating microscope.…”
Section: Delivery Systems and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation